2011
DOI: 10.3892/ol.2011.415
|View full text |Cite
|
Sign up to set email alerts
|

CD133, OCT4, and NANOG in ulcerative colitis-associated colorectal cancer

Abstract: Abstract. Stem cells are thought to contribute to tissue regeneration as well as carcinogenesis. Ulcerative colitis-associated colorectal cancer (UC-CRC) has shown distinct characteristics compared with those of sporadic CRC. The aim of this study was to evaluate the expression of stem cell markers CD133, OCT4 and NANOG in UC-CRC and the inflamed colonic epithelium of UC patients. Total RNAs of UC-CRC (n=6), inflamed colonic epithelium (n=24), sporadic CRC (n=37) and adjacent normal colonic epithelium (n=37) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…This was in line with previous investigations supporting the joint role of both biomarkers in controlling multiple pathways to govern the self-renewal characteristics and pluripotency of ESCs (60) and their positive involvement in tumor invasion and progression of many types of cancer (42,50,(61)(62)(63)(64). However, the functional impacts of both markers' coexpression in HCC need to be further explored, especially in our case, as a high level of NANOG expression was significantly associated with late-stage versus early-stage HCC compared to OCT3/4.…”
Section: Discussionsupporting
confidence: 77%
“…This was in line with previous investigations supporting the joint role of both biomarkers in controlling multiple pathways to govern the self-renewal characteristics and pluripotency of ESCs (60) and their positive involvement in tumor invasion and progression of many types of cancer (42,50,(61)(62)(63)(64). However, the functional impacts of both markers' coexpression in HCC need to be further explored, especially in our case, as a high level of NANOG expression was significantly associated with late-stage versus early-stage HCC compared to OCT3/4.…”
Section: Discussionsupporting
confidence: 77%
“…However, to the best of our knowledge, only one report has investigated the behavior and distribution of CD133 expression in UC-CRC and dysplasia, and the role of CD133 in the inflammation-dysplasia-carcinoma sequence has not been fully investigated. Specifically, Yasuda et al investigated CD133 expression in UC-CRC and inflamed colonic epithelium using real-time reverse-transcription polymerase chain reaction, and demonstrated that the level of CD133 expression in inflamed colonic epithelium was significantly lower in patients with UC with a longer duration of disease than in those with a shorter duration (19). They also examined CD133 expression in a small number (n=6) of UC-CRC cases.…”
Section: Discussionmentioning
confidence: 99%
“…Oct4 expression was significantly increased in GC tissues and its overexpression was found to be correlated with poor clinical prognosis . Overexpression of Oct‐4 has also been observed in sporadic colorectal cancer than those in adjacent normal colonic epithelium . Wen et al.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Oct-4 has been revealed that it associated with the development, transformation, and metastasis of the tumours. 12 In addition, in a study by Yasuda et al, 13 have reported the high expression of Oct-4 on sporadic colorectal cancer. Moreover, another study by Wen et al 14 indicated the upregulation of Oct-4 was upregulated in metaplastic pancreatic ducts compared with normal acini and pancreatic carcinoma.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation